Un estudio de casos: caracterización de las demandas fisiológicas, cinemáticas y neuromusculares de un árbitro de balonmano durante la competición - Garcia Santos, D.; Martin Gamonales Puerto, J.; Leon Guzmán, K.; Mancha, D.; Munoz Jimenez, J. (Revista Ciencia del Deporte, 2017)
The present study aims to know and characterize performance loads of the Handball referees during the competition. Two referees who have participated in the school league of the Extremadura Handball Federation compose the sample. Both referees have been compared in relation to internal load (Heart Rate) and external load variables (kinematic and neuromuscular performance). The results show that there are no significant differences between the two referee in any variables, and allow defining the performance requirements of Handball referees. This research line should be continued in future publications to establish individualized training programs for that population.